Synthesis Epoxy Fatty Acid Methyl Ester Using Combined Acid Catalyst - Hendriyana; Diva Amerya Agustin; Akmal Rahmawan (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2025)
Epoxy plasticizer compounds can be produced from fatty acid methyl esters through an epoxidation reaction. In this study, synthesis was carried out in a batch reactor at an operating temperature of 60oC using hydrogen peroxide as the oxygen donor. Acidic catalysts, including formic acid, acetic acid, and their combination, were applied to evaluate reaction performance. Performance was assessed based on iodine value and carbon double bond conversion, supported by physical properties such as viscosity, density, and flash point. The use of formic acid resulted in the highest conversion of 87.47% with an iodine value of 5.84g I2/100 g at a catalyst concentration of 10 wt%. Acetic acid achieved a maximum conversion of 68.96 percent with an iodine value of 14.57g I2/100 g at a catalyst concentration of 20wt%. For the mixed catalyst system, the highest conversion reached 79.30 percent with an iodine value of 9.64g I2/100 g at a total catalyst concentration of 15 wt% and a formic acid to acetic acid ratio of 30 to 70. Overall, formic acid was identified as the most effective catalyst due to its superior conversion efficiency at lower concentrations. Product analysis confirmed the formation of methyl 9,10 epoxyoctadecanoate with a yield of 12.3wt%.